1999
DOI: 10.1210/jcem.84.2.5460
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Suppression of Insulin Secretion and Gene Expression in Human Pancreatic Islets: Implications for the Development of Adipogenic Diabetes Mellitus1

Abstract: Previously we demonstrated the expression of the long form of the leptin receptor in rodent pancreatic beta-cells and an inhibition of insulin secretion by leptin via activation of ATP-sensitive potassium channels. Here we examine pancreatic islets isolated from pancreata of human donors for their responses to leptin. The presence of leptin receptors on islet beta-cells was demonstrated by double fluorescence confocal microscopy after binding of a fluorescent derivative of human leptin (Cy3-leptin). Leptin (6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(39 citation statements)
references
References 53 publications
1
37
0
1
Order By: Relevance
“…This is easily understood, since leptin has been proven to regulate insulin secretion and action through LEPRs in pancreatic β cells [31]. Chiu et al [30] found that subjects with at least one G allele had insulin-resistant phenotypes, with higher total LDL-C and higher plasma insulin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…This is easily understood, since leptin has been proven to regulate insulin secretion and action through LEPRs in pancreatic β cells [31]. Chiu et al [30] found that subjects with at least one G allele had insulin-resistant phenotypes, with higher total LDL-C and higher plasma insulin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…␤ cells express leptin receptors, and leptin inhibits insulin secretion in vivo and in vitro (17)(18)(19)(20)(21)(22)(23). In rodent islets, leptin induces ␤ cell proliferation and protects from FFAinduced ␤ cell apoptosis (24)(25)(26)(27).…”
mentioning
confidence: 99%
“…Although the hypothalamus is considered the main target for leptin, particularly with respect to body weight regulation, it is clear that this hormone has distinct actions on other peripheral, target organs. There have been several reports that leptin reduces insulin secretion from pancreatic beta cells (3)(4)(5)(6), although this view is not shared by all investigators (7). One mechanism proposed to explain the leptin-induced reduction in insulin secretion is via activation of ATP-sensitive K ϩ (K ATP ) channels (8,9).…”
mentioning
confidence: 99%